THE (O-C) DIAGRAMS OF ECLIPSING BINARIES: TRADITIONAL AND NEW WAYS OF TREATMENT - Rovithis-Livaniou, H. (Одеські астрономічні публікації, 2017)
In this review, the traditional and the new ways of treatment of the orbital period changes of close eclipsing binaries are presented. Moreover, a comparison is made, and a general discussion is given. All methods are described, in a more or less detail way, and examples are given to prove the inadequacy of the traditional methods. The latter are not only very simple and extremely restrict, but they violate the uniqueness of the solutions. Moreover, it is shown that, although sometimes traditional methods give results close to that found by the continuous methods, and because of this some could conclude that the results coming out from the classic methods and the new ones are equivalent (within observational errors), this is not the case. The big and important difference between traditional and new ways of the (O-C) diagrams’ analysis, is their physical interpretation, which in the new ways of treatment is consistent with the physics of close eclipsing binaries and with the physical mechanisms which could produce the observed orbital period variations.